Nursing in Bioethical Contact of the use of medicinal plants by pregnant women: the role of nurses in the use of phytotherapy during pregnancy (Research, Society and Development, 2020)
Objective: to identify the evidence in the literature in the period from 2010 to 2020 about the role of nurses regarding the use of medicinal plants during pregnancy. Method: this is a bibliographic review of the literature (RIL), which gave rise to an article on nursing in the bioethical contact of the use of medicinal plants by pregnant women: the role of nurses in the use of phytotherapy during the gestational period. The bibliographic search was performed using the Google academic database, VHL, LILACS, ARCA Fiocruz and SciElO. Results: the main concepts addressed in the integrative literature review (RIL) are: the role of nurses in the use of herbal medicine during pregnancy, health education for pregnant women who constantly use herbal medicines, benefits and harms of the consumption of medicinal plants in gestational period, herbs most used by pregnant women, contributions from cross-cultural nursing for pregnant women. Conclusion: it was concluded that popular beliefs and myths about the non-maleficence of herbal medicines during the gestational period still have a strong influence due to the emotional state and the concern of the pregnant woman with her well-being and the health of the fetus, and that it is necessary to monitoring the nurse so that she can better instruct the pregnant woman about which herbal medicines can be used during the course of pregnancy and the correct way to prepare, thus respecting the customs and culture of each patient.